Explaining Positive Couple Interactions after Myocardial Infarction: A Qualitative Study - Mahdieh Sarhadi; Ali Navidian; Roghayeh Mehdipour-Rabori; Esmat Nouhi (Kerman University of Medical Sciences, 2022)
Background: The quality of marital relationships can impact couples' cardiovascular health directly and indirectly. Given that communication is essential for a happy marriage and plays an important role in health, this study aimed to explain the positive interactions of couples after myocardial infarction.Methods: The current study was conducted qualitatively with the participation of seven couples (patient and his or her spouse) in teaching hospitals affiliated with Zahedan University of Medical Sciences. Purposive sampling was used to select participants. Then, unstructured in-depth interviews were conducted after obtaining informed consent. The interviews were immediately transcribed and analyzed. MAXQDA 2020 was used to categorize the data, and the method proposed by Elo and Kingas was used for data analysis.Results: The analysis of the data revealed that myocardial infarction could affect the way couples interact through two main themes including empathetic union (acceptance of each other's true selves, mutual understanding, adjusting expectations, increase in cooperation and joint activities) and optimizing couples' interactions (mutual care and attention, increase in intimacy, mutual reliance).Conclusion: This study indicated that positive couple interactions affected not only marital relationships but also health status, both directly and indirectly. Therefore, the findings of this study can be used to improve nursing student education and nursing care, and would help to develop educational and supportive interventions for patients and their spouses.